Penerapan Strategi Pembelajaran Giving Questions And Getting Answers untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Akidah Akhlak Siswa Kelas VIII di MTs PPM Babussalam Teluk Bakung - Erna Sari, As’ad Badar, Zaifatur Ridha (Pusdikra-Publishing.com, 2022)
Study this aim for knowing motivation study student on learning creed Morals after application strategy of giving questions and getting answers in class VIII MTs PPM Babussalam Teluk Bakung. Study this including in study action class (Action Research). This study used a collaborative model type, namely researchers and teachers in the Akidah Akhlak study field in class VIII MTs PPM Babussalam Teluk Bakung. subject in Study Action Class VIII is sis wa class MTs MTs PPM Babussalam Teluk Bakungwith total 30 students consisted of 14 girls and 16 men . instrument in researcher this is sheet observation and appropriate questionnaire _ with procedure study with observe cycle I and cycle II. Results study show . Application strategy Giving Questions And Getting Answers Strategy can implemented with good through two cycle . this _ could is known through activities carried out by teachers and student on cycle I and cycle II experienced improvement . Results teacher observation on cycle I , namely 75% ( enough ) then to 85.71 ( good ) on cycle II. Likewise on _ observation activity students who beginning on cycle I reached score 73.33 then increase to 90 on cycle II. After implementation Motivational Giving Questions And Getting Answers Strategy study student experience enhancement from mark questionnaire in the post test 64.3% increase to 73.4% on cycle I and keep going experience enhancement on cycle II to 86.3%. So that based on these data so could concluded that Giving Questions And Getting Answers Strategy can Upgrade motivation study student on eye lesson creed Morals in Class VIII MTs PPM Babussalam Teluk Bakung. In application strategy of giving questions and getting answers, the teacher should get them more creative and more careful in choose material learning, because no all material learning in accordance with level ability think student.